Pharm D Program Accreditation, the Most Important Step towards Promotion of Pharmacy Education - Kaveh Eslami (Research Center for Rational Use of Drugs (RCRUD), 2019)
In recent years, the number of pharmacy schools in Iran has increased from 9 in 1999 to more than 24. Many pharmacy students are being educated to become professional pharmacists. Monitoring the quality of education provided to the students and ensuring the continuance of this quality is critical. Given the important role of the pharmacist in the health care system, accreditation is a great way to assess this higher education and to monitor its performance. Accreditation is a process